Innovation for a low carbon economy: economic, institutional and management approaches (Cheltenham, 2008)
"This book shows that although innovations in energy systems represent a core contribution to achieving national and international energy policy goals, theoretical approaches to understanding innovation differ radically between separate disciplinary perspectives. The need for greater mutual learning between these approaches is met within this study as international academics from economic, institutional and management backgrounds share and analyse their respective approaches, knowledge and insights."